Reframe-IT+, an indicated preventive school-based intervention, reduces suicidal ideation among adolescents in vulnerable contexts in Chile - Daniel Nuñez; Daniela Meza; Javiera Andaur; Jo Robinson; Jorge Gaete (BMC Psychology)
Abstract Background Suicide prevention programs delivered in school settings have been shown to reduce suicide attempts and ideation among adolescents. School-based digital interventions targeting at-risk youth are a promising avenue for suicide prevention, and some evidence has shown that blending digital and face-to-face components may improve the effectiveness. However, further evidence is needed, especially in Latin America, where mental health support is limited. We tested the effectiveness of the Reframe-IT+, a blended cognitive behavioral indicated intervention to reduce suicidal ideation, designed to be delivered in school settings. It includes 13 sessions, combining eight internet-based sessions and five face-to-face sessions. Methods We conducted a cluster RCT and delivered the Reframe-IT + among secondary students attending Years 9–11. We recruited 21 schools that were randomized into two groups: (1) Intervention Reframe-IT + Group (IG) (n = 863) and (2) Control Group (CG) (n = 683). All consented students completed online screening self-reported questionnaires at baseline. The primary outcome was suicidal ideation . Additionally, we tested the impact of the intervention on depressive and anxiety symptoms, hopelessness, and emotion regulatory strategies, including social solving-problems skills, behavioral activation, cognitive reappraisal, and emotion suppression. A total of 303 students (IG, n = 164; CG, n = 139) were identified as at risk and eligible for inclusion in the study. From those, 224 students (IG, n = 123; CG, n = 101) and their caregivers were interviewed to confirm inclusion and exclusion criteria. Finally, 48 and 47 students were allocated to control and intervention groups, respectively, and answered the online questionnaires at post-intervention. We performed an intention-to-treat analysis using repetitive measures and multilevel regression analyses. Results We found a significant reduction in suicidal ideation (b=-6.7, p = 0.015, Cohen´s d = 0.49), depressive (b=-3.1, p = 0.002, Cohen´s d = 0.81) and anxiety (b=-2.60, p < 0.001, Cohen´s d = 0.72) symptoms, and hopelessness (b=-3.7, p < 0.001, Cohen´s d = 0.70) in the intervention group compared to the control group at post-intervention. We also found improvement in solving-problems skills (b=-1.6, p = 0.002, Cohen´s d = 0.58), behavioral activation (b = 2.8, p = 0.019, Cohen´s d = 0.47), and cognitive reappraisal (b = 2.2, p = 0.029, Cohen´s d = 0.53). In the exploration of the intervention mechanisms concerning suicidal ideation, the total indirect effect of the intervention (b = -5.727923; p = 0.008) was significant, whereas the direct effect (b = − 0.03195473, p = 0.903) was not significant (Suppl 2, Table 1). Problem-solving skill (b=-2.84, p = 0.016) was a significant mediator of intervention effects on suicidal ideation (Path a*b). Conclusions This is the first clustered RCT evaluation of the effectiveness of a blended indicated intervention to prevent suicidality in school settings in Latin America. This is the first step to informing policymakers to scale up an effective intervention for an important public health problem. Trial registration Clinical Trials NCT05229302. Registered on January 27th, 2022.